Phenotypic and Genotypic Analysis of Resistant Helicobacter pylori Strains Isolated from Children with Gastrointestinal Diseases - Biernat, Monika Maria (Diagnostics (Basel), 2020)
Antibiotic resistance of Helicobacter pylori is currently a global issue. The aim of this study was to analyze actual antibiotic resistance rates of H. pylori strains isolated from children with primary infections and to compare the incidence of mutations that determine resistance to clarithromycin (CH) and metronidazole (MET) in children with different clinical diagnoses. A total of 91 H. pylori strains were isolated from 108 children with primary infections. Drug susceptibility testing of the strains was performed using E-test method. Classical sequencing of DNA fragments was used to detect point mutations for CH and MET resistance. Resistance to CH was detected in 31% of isolated strains (28/91), while resistance to MET and CH was detected in 35% (32/91) of strains. A2143G was the most frequently detected mutation and was dominant among strains isolated from children with peptic ulcer disease (80%). Mutations in the rdxA gene were found significantly more frequently among MET-resistant strains than MET-sensitive strains (p = 0.03, Chi(2) = 4.3909). In children, a higher frequency of H. pylori multiresistant strains was observed compared with the previous study in the same area. Differences were found in the occurrence of point mutations among H. pylori strains resistant to CH isolated from children with different clinical diagnoses.